MEASURES TO COUNTERACT MODERN METHODS OF FRAUD AGAINST THE POPULATION - Maria S. Tikhomirova; Arina D. Palatnikova (Russian Studies in Law and Politics)
In the context of developing technologies, the risk of losing money through deception or abuse of trust increases significantly. In the modern world, scammers are finding more and more sophisticated ways to illegally seize other people's money. The article examines modern methods of committing fraud, analyzes measures to combat these crimes, puts forward proposals for updating and improving methods and measures aimed at countering modern methods of fraud.